Return to Play (RTP) and Performance in the Women's National Basketball Association (WNBA) Following Anterior Cruciate Ligament (ACL) Reconstruction (194). Issue 10 (31st October 2021) - Tramer, Joseph; Khalil, Lafi; Ziedas, Alexander; Abbas, Muhammad; Mehran, Nima; Okoroha, Kelechi
Objectives: The incidence of ACL injuries in WNBA athletes has been on the rise, despite the high rates of ACL injury there is a paucity of recent research examining the effect of ACL reconstruction on RTP and performance in these athletes. This cohort study seeks to quantify the effect of ACL reconstruction on RTP and performance on WNBA athletes. Methods: All ACL tears sustained in the WNBA from 1997-2018 were identified. BMI, age and position at the time of injury were collected for each player. RTP rates were calculated and performance data was collected for each player before and after injury to determine changes in playing time and statistical performance. Players who successfully RTP after ACL reconstruction were compared to a group of healthy controls who were matched by age, years of experience, position, height, and BMI. Statistics at one year and three years' post-injury were compared to assess acute and longitudinal changes in performance relative to pre-injury baseline. Results: A total of fifty-nine WNBA players sustained an isolated ACL tear during the study period. Forty-one (69.5%) were able to RTP. There was no difference in demographic characteristics between forty-one players and matched controls. Following RTP athletes played an average of 7.5±12.8 fewer games, 5.1±9.2 fewer minutes per game, and scored 3.7±5.0 less points per game in their first year compared to the year prior to injury. (Table1) When compared to matched controls, WNBA players returning from ACL reconstruction demonstrated a significant decline in games played, games started, minutes per game, rebounds, assists, and blocks per game in their first season after RTP. These differences resolved by year three post-surgery (Table 2). Conclusions: There is a high RTP rate following ACL reconstruction in WNBA athletes. Players may experience a decrease in playing time and performance initially when returning to play, however these variables were found to return to baseline over time.